Wigner‐Smith delay times and the non‐Hermitian Hamiltonian for the HOCl molecule. Issue 2 (1st June 2012) - Barr, A.M.; Reichl, L.E.
Abstract: We construct the scattering matrix for a two‐dimensional model of a Cl atom scattering from an OH dimer. We show that the scattering matrix can be written in terms of a non‐Hermitian Hamiltonian whose complex energy eigenvalues can be used to compute Wigner‐Smith delay times for the Cl‐OH scattering process. We compute the delay times for a range of energies, and show that the scattering states with the longest delay times are strongly influenced by unstable periodic orbits in the classical dynamics.